2021
DOI: 10.1111/bph.15582
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on pregnancy and therapeutic drug development

Abstract: Emerging data shows pregnant women with COVID‐19 are at significantly higher risk of severe outcomes compared to non‐pregnant women of similar age. This review discusses the invaluable insight revealed from vaccine clinical trials in women who were vaccinated and inadvertently became pregnant during the trial period. It further explores a number of clinical avenues in their management and proposes a drug development strategy in‐line with clinical trials for vaccines and drug treatments for the drug development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 94 publications
(121 reference statements)
0
9
0
Order By: Relevance
“…IgG antibodies to the SARS-CoV-2 virus cross the placenta, which is why immunization against this virus is recommended for women in the reproductive period [ 75 ]. Comparing vaccinated and unvaccinated gravid women, Lin et al detected different expressions of the seven miRNAs [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…IgG antibodies to the SARS-CoV-2 virus cross the placenta, which is why immunization against this virus is recommended for women in the reproductive period [ 75 ]. Comparing vaccinated and unvaccinated gravid women, Lin et al detected different expressions of the seven miRNAs [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, hypertensive pregnancy syndrome was the most frequent maternal complication (17.5%), similar to previous reports [ 21 , 27 ]. Hypertensive disorders of pregnancy and COVID-19 share an exaggerated inflammatory response, guided by cytokines such as IL-6, TNF-α and IFN-γ leading to endothelial damage [ 28 ]. Likewise, studies in Latin America [ 21 ] and other regions of the world [ 14 16 , 29 ] found that preterm delivery and low birth weight were the most frequent perinatal complications in our patient population, which could be associated with excessive host inflammatory response to COVID-19 and poor foetal vascular perfusion of the placenta [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 59 (73.8%) survived and 21 (26.2%) died. The median (IQR) age of pregnant women was 29 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) years; most were of mixed race (85%; n = 68) and in the third trimester of pregnancy (81.2%; n = 65). No statistically significant differences were found between the epidemiological and gynaecobstetric characteristics of the surviving and dead pregnant women (Table 1).…”
Section: Epidemiological and Gynaecobstetric Characteristics And Medi...mentioning
confidence: 99%
See 1 more Smart Citation
“…This, coupled with the increased transmissibility of new variants and relaxing of social distancing restrictions, contributed to the surge in hospital admissions seen in successive waves. Concerns around the longer term effect of covid-19 post partum, including long covid, cardiovascular complications of covid-19, and widening socioeconomic disparities are also mounting 6. Despite a desperate need for treatments, pregnant women continue to be left behind.…”
mentioning
confidence: 99%